EXPERIMENTAL SUBSTANTIATION OF EFFICIENCY OF LOCAL LYMPHATIC THERAPY AT SHARP IMPASSABILITY OF INTESTINES - B. H. Matkarimov (Journals Park Publishing, 2023)
Frequency OF SHARP IMPASSABILITY OF INTESTINES makes 9 % of all sharp diseases of bodies of a belly cavity. Thus death rate, according to various authors, up to 25 %. Considering that in processes of reduction in the intoxication of an organism the leading part belongs to lymphatic system, we have decided to study opportunities of local lymphatic therapy in experimental model OF SHARP IMPASSABILITY OF INTESTINES. For realization of an object in view series of experiments on 27 not purebred dogs in weight from 12 up to 15 kg are lead.